1990
DOI: 10.1037/0012-1649.26.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Face-to-face interactions of postpartum depressed and nondepressed mother-infant pairs at 2 months.

Abstract: Depression's influence on mother-infant interactious at 2 months postpartum was studied in 24 depressed and 22 nondepressed mothex-infant dyads. Depression was diagnosed using the SADS-L and RDC. In S's homes, structured interactions of 3 min duration were videotaped and later coded using behavioral descriptors and a l-s time base. Unstructured interactions were described using rating scales. During structured interactions, depressed mothers were more negative and their babies were less positive than were nond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
326
6
36

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 493 publications
(393 citation statements)
references
References 44 publications
25
326
6
36
Order By: Relevance
“…In sum, the present study confirms that both content of speech as well as touch constitute important components of the mother-infant interaction (Cohn, Campbell, Matias & Hopkins, 1990). Depressive mood in this study was found to influence the affective quality of maternal speech, as well as touch behaviour of both mother and infant.…”
Section: Discussionsupporting
confidence: 69%
“…In sum, the present study confirms that both content of speech as well as touch constitute important components of the mother-infant interaction (Cohn, Campbell, Matias & Hopkins, 1990). Depressive mood in this study was found to influence the affective quality of maternal speech, as well as touch behaviour of both mother and infant.…”
Section: Discussionsupporting
confidence: 69%
“…Mothers with PPD are observed to have significantly increased disengagement, negative affect, flatness of affect, irritation, tenseness, annoyance, and intrusiveness toward the infant on the one hand, and significantly less warmth, delight, positive regard, sensitivity, activity, contented facial expressions, imitative behaviors, contingent responses, and game-playing on the other. In addition to exhibiting more negative emotions and fewer positive emotions toward their infants, mothers with PPD are less responsive and less sensitive to infant cues, have failed to attain a successful maternal role, and have infants that are less securely attached (Beck 1995(Beck , 1996bCohn et al 1990Cohn et al , 1991Field et al 1985;Fowles 1996;Hoffman and Drotar 1991;Murray 1991;Murray and Cooper 1996). By being less responsive and less sensitive to infant cues, mothers with PPD are clearly mothering less.…”
Section: The Defection Hypothesis Part Two: Reduce Costsmentioning
confidence: 99%
“…Furthermore, Kuczynski (1984) found that depressed parents were more likely to choose discipline strategies that required less cognitive effort and tended to become overly permissive or authoritarian rather than taking the time and effort to negotiate or talk things through. Cohn, Campbell, Matias, and Hopkins (1990) showed that depressed mothers tended to be more irritable and hostile in their interactions with their children. McLoyd (1990) found that poverty and economic loss (which can occur after separation) can lead to less supportive, less consistent, and less involved parenting.…”
Section: Extant Literature -Mental Health and Parenting Variablesmentioning
confidence: 99%
“…This suggests that males" (and to a lesser degree females") mental health trajectory post-separation is associated with the quality and quantity of their relationship with their child/ren post-separation. Previous research suggests that a worse relationship with the child/ren post-separation is associated with poorer mental health (Bokker et al, 2006;Cohn et al, 1990;Lyons-Ruth et al, 2000;Weissman & Paykel, 1974).…”
Section: The Relationship Between Mental Health and Parenting Variablesmentioning
confidence: 99%